2012
DOI: 10.1177/0146167212446938
|View full text |Cite
|
Sign up to set email alerts
|

Why Anger and Disappointment Affect Other’s Bargaining Behavior Differently

Abstract: In two experiments, the authors investigated the interpersonal effects of anger and disappointment in negotiations. Whereas previous research focused on the informational inferences that bargainers make based on others' emotions, this article emphasizes the importance of affective reactions. The findings of this study show that anger evoked a complementary emotion (fear) in targets when reported by a high-power bargainer but evoked a reciprocal emotion (anger) when reported by a low-power bargainer. This recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 59 publications
(95 reference statements)
6
54
1
Order By: Relevance
“…It conveys an appraisal of the situation's perceived injustice and attribution of outgroup blame (Frijda et al, 1989;Montada & Schneider, 1989). However, research from the social-functional approach has demonstrated that although induced guilt in a receiver is a complementary emotion of a sender's expressed disappointment, induced anger in a receiver is a reciprocal emotion of a sender's expressed anger (Lelieveld et al, 2012;Lelieveld, Van Dijk, Van Beest, Steinel, & Van Kleef, 2011). We therefore expected the effect of the outgroup's disappointment expression to induce collective guilt rather than outgroup-directed anger.…”
Section: Studymentioning
confidence: 97%
See 4 more Smart Citations
“…It conveys an appraisal of the situation's perceived injustice and attribution of outgroup blame (Frijda et al, 1989;Montada & Schneider, 1989). However, research from the social-functional approach has demonstrated that although induced guilt in a receiver is a complementary emotion of a sender's expressed disappointment, induced anger in a receiver is a reciprocal emotion of a sender's expressed anger (Lelieveld et al, 2012;Lelieveld, Van Dijk, Van Beest, Steinel, & Van Kleef, 2011). We therefore expected the effect of the outgroup's disappointment expression to induce collective guilt rather than outgroup-directed anger.…”
Section: Studymentioning
confidence: 97%
“…Research has already shown that disappointment induces complementary emotions of guilt among observers in the interpersonal contexts (Lelieveld, Van Dijk, Van Beest, & Van Kleef, 2012). In the intergroup context, perceiving the ingroup as responsible for immoral actions that harmed the outgroup can potentially evoke collective guilt even among individuals who were not personally involved in the transgressions (Branscombe & Doosje, 2004;Branscombe, Doosje, & McGarty, 2002).…”
Section: Social Function Of Disappointment In Intergroup Conflictmentioning
confidence: 99%
See 3 more Smart Citations